2016
DOI: 10.1507/endocrj.ej15-0642
|View full text |Cite
|
Sign up to set email alerts
|

GNAS mutations in adrenal aldosterone-producing adenomas [Rapid Communication]

Abstract: Abstract. Mutations in GNAS, which encodes Gsα, have been documented in detail, particularly in human pituitary GHsecreting adenomas. Mutations have also recently been reported in adrenal cortisol-producing adenomas (CPAs), in addition to those in the PRKACA gene. However, mutations have not yet been examined in aldosterone-producing adenomas (APAs). Therefore, we herein investigated mutations in the GNAS gene in APAs. Two of the 15 (13%) CPAs with overt Cushing's syndrome and one of the 9 (11%) CPAs with subc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 22 publications
(37 reference statements)
2
16
0
Order By: Relevance
“…As noticed, the prevalence of KCNJ5 mutations is higher in Asia than in Western countries. We first confirmed previous findings showing a high prevalence of the KCNJ5 gene (76.3%) in Japanese patients with APAs after the addition of recent cases [7,[11][12][13]. In addition, Kitamoto et al reported a prevalence of 69.4% in Japanese [31], 59.5% in Taiwanese [29], 71.2% in Korean [30], and 76.8% in Chinese patients with APAs [28].…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…As noticed, the prevalence of KCNJ5 mutations is higher in Asia than in Western countries. We first confirmed previous findings showing a high prevalence of the KCNJ5 gene (76.3%) in Japanese patients with APAs after the addition of recent cases [7,[11][12][13]. In addition, Kitamoto et al reported a prevalence of 69.4% in Japanese [31], 59.5% in Taiwanese [29], 71.2% in Korean [30], and 76.8% in Chinese patients with APAs [28].…”
Section: Discussionsupporting
confidence: 90%
“…Boulkroun et al, who examined the large number of APA cases to date, 380, found that 129 patients (34%) had mutations in Europe [9]. We found a higher frequency, 24 out of 33 (approximately 73%) APAs, in Japan [7,[11][12][13]. Several differences of clinical features have been reported between Japanese and Western APA patients.…”
Section: Immunohistochemistrysupporting
confidence: 56%
See 3 more Smart Citations